Prognostic Value of Cerebrospinal Fluid and Serum Neurofilament Light Chain in Amyotrophic Lateral Sclerosis: A Correlation Study - Siqi Dong; Xiaoni Liu; Yanni Zhou; Jiatong Li; Zihan Qi; Zihan Wang; Wenbo Yang; Xiangjun Chen (Brain and Behavior)
ABSTRACT Background The diagnostic and prognostic values of serum neurofilament light chain (sNfL), in comparison to cerebrospinal fluid (CSF) neurofilament light chain (cNfL), and other clinical parameters in amyotrophic lateral sclerosis (ALS) at the time of diagnosis remain elusive. Methods We examine paired serum and CSF samples from 80 ALS patients and 21 control subjects, all obtained at the time of diagnosis. Additional serum samples were collected from 51 other ALS patients. NfL concentrations were quantified using the single molecule array (Simoa) technique. Results Our findings demonstrate a robust correlation between NfL levels in matched CSF and serum samples. Notably, both sNfL (p < 0.0001) and cNfL (p < 0.0001) exhibited significantly elevated levels in ALS patients compared to controls. Furthermore, baseline sNfL concentrations, as well as cNfL levels, emerged as predictive indicators of subsequent disease progression rate (sNfL: p < 0.0001, cNfL: p = 0.0005) and overall survival (sNfL: p = 0.0073, cNfL: p = 0.0044). Employing a Cox regression model, we identified baseline sNfL level (HR = 1.01, p = 0.013), and diagnostic delay (HR = 0.94, p = 0.003) as independent prognostic factors for mortality. Furthermore, we constructed a nomogram model that incorporates both sNfL and pertinent clinical variables, which substantially enhances the accuracy of predicting disease outcomes (Concordance Index, 0.808). Conclusion Our study underscores the robust correlation between sNfL and cNfL in ALS patients and establishes baseline sNfL as a potent and independent prognostic marker for mortality.